STUDI PENGARUH PENGGILINGAN KONDISI KERING DAN BASAH TERHADAP KINETIKA DAN KARAKTERISTIK DISTRIBUSI UKURAN BUTIR BIJIH SULFIDA KOMPLEKS GALENA SFALERIT – UJI PENDAHULUAN - Indah Pratiwi; Edy Sanwani (Jurnal Teknologi Mineral dan Batubara, 2023)
Grinding is generally carried out in wet conditions, but issues regarding water conservation and high-water treatment costs encourage the application of grinding in dry conditions. Both produce products with certain characteristics that affect the success of the next process. Grinding of P100 6 mesh (3.36 mm) ore was performed using steel ball media with dry and wet grinding with 33.33% solids for 5, 10, 15, 20, 25, and 30 minutes. Particle size distribution of the grinding product was obtained from the wet sieving process and the -200 mesh (-75µm) ore particles were analyzed using a laser diffraction particle size analyzer. The Alyavdin grinding kinetics equation model was used to study the kinetics of ore grinding behavior and the particle size distribution and its characteristics consisting of uniformity index, size modulus and fractal dimension were studied using the logistic, Rosin-Rammler (RR) and Gates-Gaudin-Schuhmann (GGS) equation model. Equivalent particle size (EPS) and specific surface area (SSA) observations were carried out on the -200 mesh (-75µm) grinding product. Grinding in dry condition is more effective in reducing the size of complex galena-sphalerite sulphide ore, indicated by high grinding rate with the highest K value of 0,135/minute, high cummulative % undersize, low size modulus, high uniformity index, high fine particle and high SSA compared to wet grinding. Alyavdin's kinetics model can describe the grinding kinetics of galena sphalerite complex sulfide ore, while the particle size distribution follows the logistic equation model.